2007
DOI: 10.1002/path.2259
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage involvement in the kidney repair phase after ischaemia/reperfusion injury

Abstract: Macrophage infiltration is a common feature of the early phase of renal ischaemia/reperfusion injury. Indeed, it is generally regarded as the cause of tissue injury in this phase, although it is also clear that it can lead to tissue repair in other phases. In order to ascertain whether macrophages are directly involved in the repair/late phase, which follows the proinflammatory and injury process of renal ischaemia/reperfusion, we used two different approaches based on macrophage depletion. Firstly, we produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
94
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 21 publications
9
94
0
2
Order By: Relevance
“…A study preceding that of Jung et al from the same group demonstrated that renal regeneration, prompted by mediators including IL-10, occurs only following, and not during, ischemia/reperfusion injury. 46 This segregation of the two inflammatory arms, with respect to the inflammatory milieu, is consistent with our understanding of the transition in macrophages, which secretes both IL-6 and IL-10, from a state that promotes injury to one that initiates repair. 47 Our study also expands on the literature of these cytokines in the perioperative setting, which has generally been conducted with small cohorts, in single-center settings, and with lack of defined hard outcomes.…”
Section: J Am Soc Nephrol 26: 3123-3132 2015supporting
confidence: 80%
“…A study preceding that of Jung et al from the same group demonstrated that renal regeneration, prompted by mediators including IL-10, occurs only following, and not during, ischemia/reperfusion injury. 46 This segregation of the two inflammatory arms, with respect to the inflammatory milieu, is consistent with our understanding of the transition in macrophages, which secretes both IL-6 and IL-10, from a state that promotes injury to one that initiates repair. 47 Our study also expands on the literature of these cytokines in the perioperative setting, which has generally been conducted with small cohorts, in single-center settings, and with lack of defined hard outcomes.…”
Section: J Am Soc Nephrol 26: 3123-3132 2015supporting
confidence: 80%
“…In many settings regeneration of the kidney is macrophage dependent, evidenced by the switch of macrophage phenotype from a pro-inflammatory to an anti-inflammatory phenotype, 21 which is followed by the production of angiogenic and anti-inflammatory factors in addition to phagocytic tissue remodeling. 22,61 The precise phenotype of the macrophages seen in the repairing kidney in our study does not strictly conform to the M1/M2 dichotomy, because we see expression of genes associated with both extremes and the profile changes with time. Mosser and Edwards 48 have suggested a third macrophage classification, associated with wound healing, that is distinct from the M2 category.…”
Section: Discussionmentioning
confidence: 67%
“…Recent studies in other forms of immune-mediated renal injury raise the possibility that it is the effector phenotype of the recruited macrophages rather than their presence alone that determines the extent of renal parenchymal injury. 13,14 Macrophages exhibit a range of phenotypes, a phenomenon that has been described as macrophage polarization or heterogeneity. [15][16][17] The "classically" activated or F4/80 ϩ…”
mentioning
confidence: 99%